Potential Value of Cerebrospinal Fluid Progranulin in the Identification of Postoperative Delirium in Geriatrics Patients Undergoing Knee Replacement: The Perioperative Neurocognitive Disorder and Biomarker LifestylE Study - Wang, Bin; Sun, Xiujie; Wang, Jiahan; Deng, Xiyuan; Lin, Yanan; Liu, Fanghao; Dong, Rui; Lin, Xu; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
Objective: The aim of this study was to investigate whether progranulin (PGRN) levels in cerebrospinal fluid (CSF) were associated with postoperative delirium (POD) in geriatric patients undergoing knee replacement. Method: A total of 600 Han Chinese patients aged 65–90 years and who underwent unilateral total knee arthroplasty were included in the Perioperative Neurocognitive Disorder And Biomarker LifestylE (PNDABLE) study from June 2020 to November 2020. All participants were assessed using the Confusion Assessment Method and the Memorial Delirium Assessment Scale on postoperative days 1–7 (or before discharge) by an anesthesiologist. CSF PGRN and CSF biomarkers of POD were measured by ELISA. We analyzed the risk and protective factors of POD using the multivariate logistic regression, and the associations between CSF PGRN and CSF biomarkers of POD using multiple linear regression. We also explored whether the influence of CSF PGRN on POD was mediated by POD core pathology in linear regression models. Results: Postoperative delirium incidence was 9.7% (53/545). There were significant differences in preoperative CSF PGRN between patients with POD and non-POD (NPOD). As for CSF biomarkers, CSF Aβ40, T-tau, and P-tau were risk factors for POD, while CSF PGRN, Aβ42, and Aβ42/Aβ40 were protective factors for POD, as shown by the multivariate logistic regression analysis. CSF PGRN was positively associated with CSF Aβ42 and was negatively associated with CSF Aβ40, T-tau, and P-tau in patients with POD. We found that the AUC was 0.795 (95% CI = 0.706, 0.867) for PGRN between POD and NPOD groups. We found the influence of CSF PGRN on POD was mediated by POD core pathology. The effect was considered partial mediation with the proportion of mediation varying from 44.92 to 62.07%. Conclusion: Cerebrospinal fluid PGRN may be a reasonably good prognostic factor for POD development. Overall, amyloid pathology and tau protein might partially mediate the influence of PGRN on POD. Clinical Trial Registration:www.clinicaltrials.gov, identifier ChiCTR2000033439.